Urbanization, Land-Use Conversion, and the Ambivalence of Modernization: Rural Social Transformation in Indonesia - Putra, Raafi Herdiansyah; Rodi, Moh.; Muryanti, Muryanti (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2026)
This study analyzes rural social transformation resulting from urbanization and land-use conversion in Indonesia by examining the case of Cipagalo Village, Bojongsoang Subdistrict, Bandung Regency, West Java. Drawing on modernization theory, the study critically examines how the transition from agrarian livelihoods to an industrial–service economic structure does not unfold as a linear and integrative process, but instead generates ambivalent and uneven social dynamics. Using a qualitative approach that combines in-depth interviews, field observations, and document analysis, the study captures longitudinal social change based on the lived experiences of long-term village residents. The findings reveal three main patterns. First, urbanization and land conversion operate as mechanisms of rural economic restructuring that shift agrarian livelihoods toward construction, retail, and service sectors, while simultaneously weakening local community control over strategic resources and reinforcing dependence on market mechanisms and informal employment. Second, these economic transformations reconfigure village social relations, marked by the erosion of gotong royong as an organic social practice, the rise of individualistic and digitally mediated orientations, and the gradual weakening of communal solidarity and local cultural norms. Third, the acceleration of urbanization produces new socio-ecological vulnerabilities, including spatial conflicts, environmental crises, and heightened insecurity, reflecting processes of social disorganization within transitional rural spaces. These findings underscore that urbanization and land-use conversion embody the ambivalence of modernization in rural Indonesia, simultaneously opening economic opportunities while generating structural tensions and social vulnerabilities. This study contributes to rural sociology by offering a critical reading of modernization as a multidimensional, contextual, and power-laden process in peri-urban regions.